Metabolic Plasticity of Melanoma Cells and Their Crosstalk With Tumor Microenvironment - Avagliano, Angelica; Fiume, Giuseppe; Pelagalli, Alessandra; Sanità, Gennaro; Ruocco, Maria Rosaria; Montagnani, Stefania; Arcucci, Alessandro (Frontiers in Oncology, 2020)
Cutaneous melanoma (CM) is a highly aggressive and drug resistant solid tumour, showing an impressive metabolic plasticity modulated by oncogenic activation. In particular, melanoma cells can generate adenosine triphosphate (ATP) during cancer progression by both cytosolic and mitochondrial compartments, although CM energetic request mainly relies on glycolysis. The upregulation of glycolysis is associated with constitutive activation of BRAF/MAPK signalling sustained by BRAFV600E kinase mutant. In this scenario, the growth and progression of CM are deeply affected by metabolic crosstalk between melanoma cells and tumour microenvironment (TME) that can influence metabolic choice of melanoma and sustain tumour development and immune escape. Furthermore, CM metabolic plasticity can induce a metabolic adaptive response to BRAF/MEK inhibitors (BRAFi/MEKi), associated with the shift from glycolysis toward oxidative phosphorylation (OXPHOS). Therefore, in this review article we summarize the metabolic plasticity of CM and its alterations, associated with TME changes that regulate melanoma progression, drug resistance and immunosurveillance. Finally, we describe hallmarks of melanoma therapeutic strategies targeting the shift from glycolysis toward OXPHOS.